Comparison between dexmedetomidine and propofol as sedatives for critically ill patients in intensive care units - AL-Saad, Sabah N.; Sahib AI-Jaafari, Haitham A. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Regarding using of sedation in the intensive care unit (ICU) should allow the patient to be more comfortable, calm, cooperative, and at the same time easily arousable without delay niether weaning nor prolonged mechanical ventilation. Objective: The aim of my study is to compare the effect of dexmeditomidine Versus propofol for sedation and hemodynamic stability in a critically ill patient. Patient and method: A randomized study of 44 patients admitted to ICU; 22 of them received dexmedetomidine and the other 22 patients received propofol for sedation. The level of consciousness, blood pressure, heart rate, respiratory rate and requirement for adjuvants to reach the target level of sedation were monitored for the first 12 hours. Result: By applying Null hypothesis it was found that dexmedetomidine was significantly effective when compared with propofol for sedation with a p-value less than 0.001, while it was not significantly effective when compared with propofol plus adjuvant with p-value> 0.05. Conclusion: Dexmedetomidine is effective as a sole sedative agent with haemodynamic stability without the need to add any adjuvant to it, while propofol cause hypotension and bradycardia if used alone to reach our target level of sedation, but can be used with adjuvant to reach our target of sedation and haemodynamic stability. Keywords: Dexmedetomidine, Propofol, Sedation, ICU.